The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1093/nar/gkm480
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant allele frequencies of the SNPs located in microRNA target sites are potentially associated with human cancers

Abstract: MicroRNAs (miRNAs) are a class of noncoding small RNAs that regulate gene expression by base pairing with target mRNAs at the 3′-terminal untranslated regions (3′-UTRs), leading to mRNA cleavage or translational repression. Single-nucleotide polymorphisms (SNPs) located at miRNA-binding sites (miRNA-binding SNPs) are likely to affect the expression of the miRNA target and may contribute to the susceptibility of humans to common diseases. We herein performed a genome-wide analysis of SNPs located in the miRNA-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
188
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(199 citation statements)
references
References 30 publications
10
188
0
1
Order By: Relevance
“…It also has been also reported that SNPs in miRNA-binding sites affect miRNA target expression and function and, thus, potentially are associated with cancer. 36 Although it remains to be determined whether the common variant of rs3842 in the 3 0 UTR of ABCB1 could affect gene regulation, the current case-control study indicates that this SNP may be associated with lung cancer through a possible miRNA-mediated mechanism.…”
Section: Discussionmentioning
confidence: 72%
“…It also has been also reported that SNPs in miRNA-binding sites affect miRNA target expression and function and, thus, potentially are associated with cancer. 36 Although it remains to be determined whether the common variant of rs3842 in the 3 0 UTR of ABCB1 could affect gene regulation, the current case-control study indicates that this SNP may be associated with lung cancer through a possible miRNA-mediated mechanism.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, SNPs that could affect response to miRs were noted in miR target site sequences (159,160). Correlations between miR polymorphisms and SNPs in miR target sites with risk of bladder and colorectal cancers were reported (161)(162)(163). Hence, examination of SNPs in miR-binding sites may also provide key insights into various human diseases.…”
Section: Clinical Applications Therapeutic Strategies and Perspectivesmentioning
confidence: 99%
“…30 For example, two groups have evaluated the presence of SNPs located in miRNA-binding sites of the 3 0 UTR of several genes and SNPs in the micro-RNA seed regions by genome-wide analyses. 54,55 Yu et al 54 were able to identify twelve miRNA binding SNPs that display an aberrant allele frequency in human cancers. Moreover, Saunders et al 55 were able to identify approximately 250 SNPs that create novel target sites for miRNAs in humans and may result in phenotypic differences.…”
Section: Micrornas In Complex Diseasesmentioning
confidence: 99%